Biocontrol of Sclerotinia sclerotiorum, Sclerotium rolfsii, Fusarium spp., and the agronomic performance of soybean by Trichoderma spp. - Lincon Rafael da Silva; Ana Beatriz Zacaroni; Ana Luiza Bezerra Cardoso; Angelo Aparecido Barbosa Sussel; Alexei de Campos Dianese; André Ferreira Pereira; Sueli Corrêa Marques de Mello (Revista Ciência Agronômica)
ABSTRACT Soybean (Glycine max L.) is a globally important legume that is susceptible to a variety of pathogens throughout its development stages. One effective option for controlling these diseases is the use of biological products derived from fungi of the genus Trichoderma. This study aimed to select Trichoderma strains, maintained in culture collections, as control agents for the pathogens Sclerotinia sclerotiorum, Sclerotium rolfsii, and Fusarium spp. Additionally, it sought to identify strains among those selected that can enhance the agronomic characteristics of soybean plants in the field. Experiments were carried out in vitro, in a greenhouse, and in an experimental field. The T. koningiopsis CEN209 strain showed performance in vitro and in the greenhouse against S. sclerotiorum, S. rolfsii and Fusarium spp., while the T. afroharzianum CEN230 and T. rifaii CEN288 strains obtained better performances against S. sclerotiorum and S. rolfsii. The strains T. azevedoi CEN1242 and T. koningiopsis CEN1513 significantly increased the final soybean yield under field conditions without the occurrence of soil-borne diseases.